2013
DOI: 10.1103/physrevb.88.024102
|View full text |Cite
|
Sign up to set email alerts
|

Bistability of ferroelectric domain walls: Morphotropic boundary and strain effects

Abstract: The internal structure of neutral 180• domain walls in perovskite-type ferroelectrics is studied in terms of Landau theory taking into account electromechanical coupling. The study is focused on the wall bistability, a factor of potential interest for information storage. A strong impact of elastic effects on the wall structure is demonstrated. It is shown that the conclusion derived earlier by Houchmandzadeh et al. [J. Phys.: Condens. Matter 3, 5163 (1991)], neglecting the electrostictive coupling, that all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This enables the development of ferroelectricity in the domain walls of nonferroelectric STO 39,42 , for example. In this scenario, a gradient of the order parameter exists in the walls, and gradient-gradient coupling between order parameters or with strain, can occur [43][44][45] . Lateral movement of domain walls in ferroelastics, more generally, can take place by movement of ledges along the walls 46,47 .…”
Section: Extrinsic Charactermentioning
confidence: 99%
“…This enables the development of ferroelectricity in the domain walls of nonferroelectric STO 39,42 , for example. In this scenario, a gradient of the order parameter exists in the walls, and gradient-gradient coupling between order parameters or with strain, can occur [43][44][45] . Lateral movement of domain walls in ferroelastics, more generally, can take place by movement of ledges along the walls 46,47 .…”
Section: Extrinsic Charactermentioning
confidence: 99%
“…Ferroelectric materials change domain structures but only 90 boundaries carry sufficient strain to generate AE, while the strain involved in 180 boundaries is much weaker. [23][24][25][26] Detailed computer simulations of AE in ferroelectrics have shown that most nano-structural changes in ferroic materials contain too little elastic energy to generate measurable AE signals. 27 This result also questions the way we analyze AE in ferroic materials: Visible AE events are due to a complex combination of a multitude of various domain boundary movements over a very short time interval (large jerks) and it is virtually impossible to distinguish between individual events.…”
Section: )mentioning
confidence: 99%
“…2ab) show a clear indication of the characteristic double-kink in the normal (Néel) component of the polarization (P s ). It is worth noting that in some high-symmetry domains walls, [35][36][37] such double kinks on P s or P t appear only after considering flexoelectric [34] coupling terms, while here, in the case of the [211]-oriented Bloch (bistable [38]) wall, the flexoelectric coupling has actually only a negligible influence on the domain wall profile [15,16]. In either case, the amplitude of these double-kinks (about one percent of the spontaneous polarization) is much smaller than the magnitude of the P s oscillations of Fig.…”
mentioning
confidence: 99%